EFFECT OF SUPPLEMENTATION WITH COPPER SOURCES ON BROILER PERFORMANCE,INTESTINAL MORPHOLOGY AND LIVER COPPER CONTENT - Zea M., Otto (2014)
This study aimed to evaluate the effect of different copper sources on broilerperformance, intestinal morphology and liver copper contents. Two hundred one-dayold Cobb 500 male chicks were randomly distributed into five groups, using 4 replicates and 10 birds per replicate. The treatments were: T1, basal diet containing antibiotic(positive control); T2, basal diet without antibiotic (negative control); T3, as T2 + 250ppm Cu from copper sulphate; T4, as T2 + 250 ppm Cu from copper oxychloride; T5, T2 +250 ppm Cu from tribasic copper chloride. No significant differences were found betweentreatments on final body weight, daily body weight gain, cost/benefit ratio and carcassyield. The lowest feed intake and the best feed efficiency were observed in T2 as comparedto T1 and T2 (p<0.05). The highest copper content in liver occurred in T5 (p<0.05).Copper supplements affected villus height and area in jejunum as compared to the control groups. It is concluded that supplementation with 250 ppm Cu from copper sulphateimproves feed efficiency and that copper supplementation regardless the source affectedintestinal morphology.